2011
DOI: 10.1104/pp.111.176685
|View full text |Cite
|
Sign up to set email alerts
|

WEREWOLF, a Regulator of Root Hair Pattern Formation, Controls Flowering Time through the Regulation ofFTmRNA Stability      

Abstract: A key floral activator, FT, integrates stimuli from long-day, vernalization, and autonomous pathways and triggers flowering by directly regulating floral meristem identity genes in Arabidopsis (Arabidopsis thaliana). Since a small amount of FT transcript is sufficient for flowering, the FT level is strictly regulated by diverse genes. In this study, we show that WEREWOLF (WER), a MYB transcription factor regulating root hair pattern, is another regulator of FT. The mutant wer flowers late in long days but norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 75 publications
0
32
0
Order By: Relevance
“…Like transcripts of most genes involved in developmental mechanisms, FT mRNAs are rapidly degraded (Seo et al . 2011).…”
Section: Molecular Basis Of Ft‐dependent Floweringmentioning
confidence: 99%
See 1 more Smart Citation
“…Like transcripts of most genes involved in developmental mechanisms, FT mRNAs are rapidly degraded (Seo et al . 2011).…”
Section: Molecular Basis Of Ft‐dependent Floweringmentioning
confidence: 99%
“…2011). However, a recent study showed that they are stabilized by the indirect action of WEREWOLF (WER), part of a protein complex that is only present in epidermal tissues (Seo et al . 2011).…”
Section: Molecular Basis Of Ft‐dependent Floweringmentioning
confidence: 99%
“…To probe the functional significance of the activation of root-expressed genes in the callus we chose the root stem cell maintenance regulators PLT1 and PLT2 for further analysis, as they are root-specific, unlike SCR and WER which are also expressed in the shoot [24,27,28]. We examined if PLT1 and PLT2 can be induced by PLT5.…”
Section: De Novo Shoot-promoting Activity Of Key Regulators Is Impairmentioning
confidence: 99%
“…FT might also be controlled at posttranscriptional levels, since the werewolf root hair patterning mutant indirectly affected FT mRNA stability in Arabidopsis, but the molecular basis of this process is still elusive (Seo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%